Electrocardiographic predictors of validated right ventricular outflow tract septal pacing for correct localization of transthoracic echocardiography. Issue 3 (25th March 2018) - Wei, Huiqiang; Tang, Jiaojiao; Chen, Dongli; Zhang, Qianhuan; Liang, Yuanhong; Liu, Lie; Wu, Shulin; Lin, Chunying; Yang, Zhiming; Chai, Chanjuan
Abstract : Background: Electrocardiographic (ECG) characteristics of true right ventricular outflow tract (RVOT) septal pacing have not been clearly demonstrated. Hypothesis: We hypothesized that ECG parameters would help operators differentiate true RVOT septum from non‐septal septum. Methods: We analyzed 151 patients who underwent pacemaker implantation with a ventricular lead in the RVOT. Transthoracic echocardiographic (TTE) determination of pacing sites was applied in all patients after implantation. A 12‐lead ECG was recorded during forced ventricular pacing. Results: According to TTE orientation, pacing at the RVOT septum was achieved in 94 patients (62.3%). Compared with nonseptal pacing, septal pacing had significantly shorter QRS duration (139.2 ± 18.5 ms vs 155.5 ± 14.7 ms; P  < 0.001). More frequent negative or isoelectric QRS vector in lead I (76% vs 32%; P  < 0.001), lead II/III R‐wave amplitude ratio < 1 (52% vs 25%; P  = 0.001), and aVR/aVL QS‐wave amplitude ratio < 1 (59% vs 32%; P  = 0.001) were observed in septal pacing. Transitional zone (TZ) score (3.8 ± 0.96 vs 4.2 ± 0.90; P  = 0.004) and TZ index (0.3 ± 0.5 vs 0.6 ± 0.7; P  = 0.008) were significantly lower in septal pacing than in nonseptal pacing, respectively. In multivariate analysis, paced QRS duration and negative or isoelectric QRS vector in lead I independently predicted RVOT septal pacing ( P  < 0.001). At ROC curve analysis, paced QRS duration ≤145 ms identified RVOT septal pacing with 85.1% sensitivity and 78.9% specificity. Conclusions: This study reveals the heterogeneity of lead placement within the RVOT. Narrower paced QRS duration and negative or isoelectric QRS vector in lead I independently predict RVOT septal pacing.